CORRECTING THE VOLUME OF COMMUNAL RESOURCE IN THE COMMUNAL-DWELLING SECTOR OF RUSSIA: DEVELOPING LEGISLATION AND COURT PRACTICE UNDER THE MODERN CONDITIONS - Y. A. Kantser (Russian Journal of Economics and Law)
Objective: to explore the practical issues of changes in the volume and cost of communal resources.Methods: comparative-legal, systemic, legal, logical-theoretical, structural and functional analysis.Results: recommendations have been made on the application of rules on correcting the volume of communal resources; changes and amendments to existing legislation were introduced; some theoretical conclusions can serve as the basis for methodological recommendations and be applied by the personnel of supply companies and regulatory organization (homeowners' associations), as well as regulatory authorities and courts; the research materials can be used in the process of conducting training sessions on civil and housing law.Scientific novelty: the study of the still insufficiently studied civil-legal relations in connection with the adoption of the new rules of communal services, their classification, identifying contradictions, the first comprehensive study of the existing regulation of resources supply and correcting the volumes of communal resources, generalization of judicial practice in this area.Practical significance:the results can be used by lawyers of electricity supply companies and regulatory organization in their professional activity.